2018
DOI: 10.3390/biom8030055
|View full text |Cite
|
Sign up to set email alerts
|

Developments in Cell-Penetrating Peptides as Antiviral Agents and as Vehicles for Delivery of Peptide Nucleic Acid Targeting Hepadnaviral Replication Pathway

Abstract: Alternative therapeutic approaches against chronic hepatitis B virus (HBV) infection need to be urgently developed because current therapies are only virostatic. In this context, cell penetration peptides (CPPs) and their Peptide Nucleic Acids (PNAs) cargoes appear as a promising novel class of biologically active compounds. In this review we summarize different in vitro and in vivo studies, exploring the potential of CPPs as vehicles for intracellular delivery of PNAs targeting hepadnaviral replication. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…In the former case, the inhibition of the biological target led to an increased expression of the cystic fibrosis conductance regulator (CTFR) in Calu-3 cells [ 89 ], while in the latter example the sequestration of the given miR promoted a higher expression of the p27Kip1 gene in the breast cancer MDA-MB-231 line [ 90 ]. Both octa-arginine and tetralysine tails were instead found to induce a PNA-mediated decrease of hepatitis B virus replication after intravenous administration in ducklings, with better results in terms of sequence selectivity when the polylysine moiety was conjugated to the given antisense oligomer [ 91 , 92 ].…”
Section: Pna Conjugatesmentioning
confidence: 99%
“…In the former case, the inhibition of the biological target led to an increased expression of the cystic fibrosis conductance regulator (CTFR) in Calu-3 cells [ 89 ], while in the latter example the sequestration of the given miR promoted a higher expression of the p27Kip1 gene in the breast cancer MDA-MB-231 line [ 90 ]. Both octa-arginine and tetralysine tails were instead found to induce a PNA-mediated decrease of hepatitis B virus replication after intravenous administration in ducklings, with better results in terms of sequence selectivity when the polylysine moiety was conjugated to the given antisense oligomer [ 91 , 92 ].…”
Section: Pna Conjugatesmentioning
confidence: 99%
“…The antiviral efficiency of several oligonucleotides as PNAs and siRNA can be improved by their coupling to CPPs used as vehicles. Indeed, our studies showed that CPPs considerably increased PNAs uptake into the hepatocytes in vitro in primary duck hepatocyte cells and in vivo in duckling [ 9 , 11 , 12 , 37 ]. Otherwise, other studies showed the benefit of siRNA coupling to CPPs on their intracellular delivery [ 38 , 39 ] and on their antiviral activity [ 28 , 40 ].…”
Section: Benefit Of Cpps Used As Vehicles In Oligonucleotides Delimentioning
confidence: 99%
“…The small interfering RNAs (siRNAs), are a promising approach for gene therapy, however their intracellular administration remains difficult. To date, a great variety of delivery system for siRNAs has been investigated such as lipids, polymers, aptamers and cell penetrating peptides (CPPs) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In this regard, CPPs appear as a new class of transporters, which increase intracellular uptake of biologically active molecules including siRNAs [ 45 ] ( Figure 2 ).…”
Section: Benefit Of Cpps Used As Vehicles In Oligonucleotides Delimentioning
confidence: 99%
See 2 more Smart Citations